An Overview of Ergonomic Methods to Improve Didactic Performance in the School Environment - Fošnarič, Samo (Sodobni didaktični diskurzi v kontekstu pedagoške tradicije: Monografija v počastitev 80-letnice prof. dr. Martina Kramarja, 2025)
This paper discusses the role of ergonomic methods in improving didactic effectiveness in the school environment. Firstly, the main challenges that ergonomics faces in creating an optimal learning environment are presented, followed by an overview of the main ergonomic methods (OWAS, RULA, REBA and the method of momentary observation). The article focuses mainly on the physical parameters of the learning environment and the tools used to assess them. It analyses the main ergonomic factors such as the spatial layout, the suitability of school furniture, the impact of environmental conditions (lighting, acoustics, thermal environment) and the use of digital resources. Based on a study of sources and various research findings, the paper summarises the theoretical aspects and shows how each factor contributes to reducing physical strain and promoting didactic effectiveness. The paper does not offer detailed practical guidance but focuses on explanations and possible research approaches for further studies on ergonomics in education. The conclusion emphasises the importance of an interdisciplinary approach and the possibilities for further studies to develop ergonomic methods adapted to the specific needs of the educational environment.